MERIT SYSTEM POLICY IN IMPLEMENTING POSITION MOVEMENTS IN THE SIMEULUE DISTRICT GOVERNMENT OF ACEH PROVINCE - Khalida Ulfa; Fajar Rahmanto; Suswanta Suswanta (DIA: Jurnal Administrasi Publik, 2020)
Merit System is the placement of someone with a high leadership position based on their competency. The government as the holder of power always makes new regulations or policies and also changes existing policies, to improve the quality of life of the people and the government institution itself. This article aims to analyze the merit system policy in the implementation of the government in Indonesia in implementing the principles of good governance and to see how the role of Baperjakat in making the mutation decision letter has caused problems between ASN and the Regent of Simeulue. The research method uses descriptive qualitative through literature review and research information. Sources of data obtained through journals, news, and documents. Data analysis techniques using Nvivo plus 12 analysis in the form of the crosstab. The results showed that the procedure for the policy of the position of the State Civil Apparatus (ASN) issued by the Regent of Simeulue was not based on established rules. In the process of mutation, the basic foundation of its implementation is still to use the seniority system and the spoil system where this system is not well used in the mutation process. In this mutation, the application is not by the principles of good governance.